New bracketing luminescence ages constrain the Sima de los Huesos hominin fossils (Atapuerca, Spain) to MIS 12. Issue 131 (June 2019) - Demuro, Martina; Arnold, Lee J.; Aranburu, Arantza; Sala, Nohemi; Arsuaga, Juan-Luis
Abstract: Recent chronological studies of the Sima de los Huesos (SH) hominin fossil site, Atapuerca, Spain, have established a close minimum age of at least 430 ka for sedimentary material immediately overlying the human remains. However, a firm maximum age limit still needs to be established for the SH fossils in order to better constrain the timing for the onset of Neandertal speciation. In the present study, we address this important chronological gap at SH by providing direct ages for the sediment deposits that host, and immediately underlie, the hominin fossils. Depositional ages were obtained using single-grain thermally-transferred optically stimulated luminescence (TT-OSL), a technique that has yielded reliable 'extended-range' luminescence chronologies at several independently dated Atapuerca sites. Four single-grain TT-OSL depositional ages of 453 ± 56 ka, 437 ± 38 ka, 457 ± 41 ka and 460 ± 39 ka were obtained for the red clay lithostratigraphic units (LU-5 and LU-6) found underlying and encasing the SH hominin bones. A Bayesian age-depth model was constructed using previously published chronologies, as well as the new single-grain TT-OSL ages for LU-5 and LU-6, in order to derive combined age estimates for individual lithostratigraphic units preserved at SH. The combined modeled ranges reveal that the hominin-bearing layer (LU-6) was deposited between 455 ± 17 ka and 440 ± 15 ka (mean lower and upper boundary 68.2% probability range ± 1σ uncertainty, respectively), with a mean age of 448 ± 15 ka. These new bracketing ages suggest that the hominin fossils at SH were most likely deposited within Marine Isotope Stage (MIS) 12, enabling more precise temporal constraint on the early evolution of the Neandertal lineage. The SH fossils represent the oldest reliably dated hominin remains displaying Neandertal features across Eurasia. These Neandertal features are first observed in the facial skeleton, including the mandible and teeth, as well as the temporomandibular joint, and appear consistently across the SH collection. Our chronological findings suggest that the appearance of these Neandertal traits may have been associated with the climatic demise of MIS 12 and the ecological changes that occurred in Iberia during this period. Other Middle Pleistocene hominin fossils from Europe dated to MIS 12–11, or later, show different morphological trends, with some lacking Neandertal specializations. The latest SH dating results enable improved temporal correlations with these contrasting hominin records from Europe, and suggest a complex picture for hominin evolution during the Middle Pleistocene.